Bibliometric analysis of the impact of environmental degradation on women and the importance of women’s representation - Y.A. Pratama; M.Y.A. Kadir; A. Rivaldi; I.C. Mulya; S. Amirah; M. Iqhrammullah (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Climate change and pollution present severe threats to the environment and human well-being. Women are disproportionately affected by health challenges, including reproduction, cardiovascular, and neurological challenges. To address this issue, gender-inclusive environmental policies must be implemented. This aspect is particularly important with a setback observed in the environmental management regulations in Indonesia, where the government ratified the Omnibus Law on Job Creation, which removes the stringent licensing process for environmentally impactful activities. This situation highlights government negligence, emphasizing the urgent necessity for enhanced women’s participation in the legislature. This study has two objectives. First, evidence of environmental impact on women’s health is subject for evaluation. Second, this study aims to highlight the urgent need for increased women’s participation in environmental policy-making and legislative processes.METHODS: This study used bibliometric analysis, examining metadata from published literature indexed in the Scopus database. The search, conducted on 10 January 2024, utilized the keywords “Women” AND “Environment” and their synonyms, covering records from 1909 to 2024. Bibliometric analysis was conducted using Biblioshiny, with network and density visualization performed using VOSviewer. The participation of women in decision-making was analyzed based on their number of seats in Parliament and a literature survey. The selection of frequently occurring keywords and clusters of keyword co-occurrence was carried out independently by two independent reviewers.FINDINGS: The bibliometric analysis included metadata from 3770 records, revealing an exponential increase in trends from 2000 to 2020. Keyword co-occurrence analysis identified eight research topic clusters focused on the environmental impact on women’s health. Thereafter, the co-occurring keywords were utilized to trace the evolution of study themes, resulting in the identification of four main themes with well-established scientific evidence: (1) air pollution impact on pregnancy and its outcome, (2) pollution impact on women’s hormones, (3) environmental impact in urban settings, and (4) heavy metal pollution. Indonesia has never achieved 30 percent women representation in Parliament, highlighting the unsatisfactory participation of women in legislative elections. The underrepresentation of women directly impacts the insufficient attention to their well-being throughout the policy-making.CONCLUSION: The environment significantly influences women’s health, potentially making the population markedly vulnerable owing to societal roles and hormonal factors. To address this issue, a crucial step is actively involving women in policy-making, particularly through a reserved seat concept in Parliament. This approach, applicable globally, acknowledges the widespread impact of environmental issues on women across countries.